Composição química e atividade biológica de extratos de plantas de Dipteryx punctata (S.F. Blake) Amshoff oriundas de Mojuí dos Campos, Pará - SOUSA, Bruna Cristine Martins de (Universidade Federal do Oeste do Pará, 2023)
The genus Dipteryx harbors species known as cumaruzeiros, belonging to the Fabaceae family and originating in Central and South American countries. Among the species of this genus, Dipteryx odorata stands out historically in the Amazon, for the supply and commercialization of multiple products such as wood and seeds, used for the extraction of coumarin, the main active compound. The species Dipteryx punctata also has a wide distribution in the North region of Brazil, however, it lacks studies that detail its phytochemical composition and biological activities. In this sense, this work aimed to evaluate the chemical profile and the antioxidant and antifungal activities of ethanolic extracts of D. punctata. A systematic review was carried out on the genus Dipteryx using SciELO and the Brazilian Digital Library of Theses and Dissertations (BDTD) as databases. For chemical and biological evaluations, plant material was collected in five areas producing cumaru seeds, in Mojuí dos Campos, Pará. The extracts were obtained via Soxhlet, using 92.8% distilled ethanol as solvent, with a total duration of eight hours, calculating the final yield. Chemical analyzes of the extracts were performed by Thin Layer Chromatography (TLC), Gas Chromatography coupled to Mass Spectrometry (GCMS), and determination of phenolics and flavonoids. Antioxidant activity was performed by scavenging DPPH free radicals. The antifungal activity of the extracts was evaluated under in vitro and in vivo conditions. In the in vitro assay, the extracts and the coumarin standard were tested at concentrations: 10%, 20%, 30%, 40% and 50% (p: v), added in potato-dextrose-agar (PDA) medium, over the fungus Colletotrichum musae, the causal agent of anthracnose disease in bananas. The control consisted of fungal growth only in PDA medium. The experimental design was completely randomized (DCR), in a factorial scheme, with four replications. The evaluations were carried out by measuring the average diameter of the colonies, daily, for eight days. With the data from the colonies, the percentage of inhibition of growth (PIG), mycelial growth velocity index (MGVI) and the growth rate (Gr) were determined. In the in vivo assay, the extracts and coumarin were tested at concentrations of 40% and 50%, in preventive and curative applications. The experimental design was completely randomized (DCR), in a factorial scheme, with three replications. The evaluations were carried out by measuring the mean diameter of the lesions at intervals of two days, up to eight days after inoculation. The data obtained in the antifungal assays were submitted to analysis of variance and compared by the Tukey test (p≤0.05), using the statistical software SISVAR 5.6. Studies on the genus Dipteryx are more restricted to the species Dipteryx alata and Dipteryx odorata. The highest yields of extracts were obtained for residues and fruit seeds. The extracts from leaves, branches, residues and seeds presented the classes of terpenes, condensed and hydrolysable tannins, flavonoids and coumarin, as well as potential antioxidant action. The extracts from the branches and residues of the fruits of D. punctata and the coumarin pattern, caused the greatest inhibitions in the growth of the phytopathogen in vitro and in vivo, all extracts were effective, with emphasis on coumarin and for the preventive applications of concentrations tested. The results obtained for the extracts are promising and sources of investigation for the future development of natural products aimed at controlling anthracnose in a more sustainable way.